Invigorating foreign aid administration: remittances' strategy, pro-poor and gender focus - Adebayo Adedokun (Financial Innovation, 2015)
Background: The pitfall of top-down approach to development is identified as a major cause of aid inefficiency. The approach is fraught with corruption and unethical practices that have bedeviled aid administration. Meanwhile, the impact of remittances has been widely acknowledged in the national development process. Methods: This study therefore reviews the extant foreign aid administrative norms and practices using various conceptual frameworks and diagrammatic representations with a view to identifying the inherent weaknesses in the process. Results: In the light of the findings, the study pitches its tent around the concept of remittances as a learning process for aid administration. Consequently, the pro-poor and gender focus approaches of remittances to development, as well as its bottom-up approach is proposed as a conceptual framework for aid administration. Conclusions: The study concludes that, strict adherence to bottom-up approaches proposed in this article would keep corruption and other unethical practices which have rendered the aid administrative process inefficient, to the barest minimum.
Keywords: 650; Foreign Aid; Remittances; Pro-Poor Aid; Gender Focus Aid